"Bringing Tap Back": Expanding the "Sodabriety" Teen Advisory Council Approach in Tennessee High Schools. (June 2021) - Smith, Laureen H.; Sexton, Courtney; Pettigrew, Kimberly; Eastburn, Sarah
Sugar-sweetened beverages (SSBs) are a large source of added sugar in teenagers' diets, comprising 20–25% of daily calories. Despite efforts, teens in rural and southern states continue to have the high SSB consumption rates. Using Teen Advisory Councils (TAC), students designed and delivered school-specific interventions at five Tennessee schools. Using repeated measures models with Bonferroni correction, data were collected on SSBs and water consumption at baseline and 30 days postintervention. The 573 participants ranged from 13 to 19 years; mean age 15.97 years ( SD = 1.4). Daily SSB servings decreased from a mean of 2.37 ( SD = 2.06) to 1.87 ( SD = 1.89; p = .024). Weekly SSB behaviors decreased 10%. Daily water consumption increased 19.5% to 4.46 ( SD = 2.97) servings ( p = .03). Student-led efforts supported behavioral changes. TACs were effective at changing lifestyle behaviors. Community-driven solutions may result in manageable changes to sustain behaviors.